The adventures of Tintin - Herge (Boston : Little, Brown, 2009)
Content. __1. Red Rackham's treasure.__2. The seven crystal ball.__3. Prisoners of the sun.
Keywords: Crime -- Fiction; Adventure and adventures -- Fiction; Cartoons and comics